2016
DOI: 10.1002/jcph.746
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacokinetic/Pharmacodynamic Relationships of Etravirine in HIV‐1‐Infected, Treatment‐Experienced Children and Adolescents in PIANO

Abstract: PIANO (NCT00665847) investigated etravirine pharmacokinetics, efficacy, and safety in children and adolescents. Treatment-experienced, HIV-1-infected patients (≥6 to <18 years) received etravirine 5.2 mg/kg twice daily (maximum 200 mg twice daily) plus background antiretrovirals. A population pharmacokinetic model was developed, and etravirine C and AUC were estimated. Relationships among intrinsic/extrinsic factors and etravirine pharmacokinetics and pharmacokinetics with pharmacodynamics were assessed. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Though rashes were reported in 46.2% of study participants in P1090, these events were grades 1 or 2 and none for which causality data were available were attributed to ETR. The risk of rash increases with increasing ETR exposure [ 8 ], thus the overall lower exposures in P1090 and small sample size may explain the lack of severe rashes in this study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Though rashes were reported in 46.2% of study participants in P1090, these events were grades 1 or 2 and none for which causality data were available were attributed to ETR. The risk of rash increases with increasing ETR exposure [ 8 ], thus the overall lower exposures in P1090 and small sample size may explain the lack of severe rashes in this study.…”
Section: Discussionmentioning
confidence: 97%
“…ETR was initially evaluated in six children in cohort I at a dose of 5.2 mg/kg twice daily based on data from the PIANO trial in children aged 6--17 years [ 8 ]. ETR exposures with this dose failed to meet the protocol-defined pharmacokinetics criteria, and thus the ETR starting dose was revised.…”
Section: Methodsmentioning
confidence: 99%
“…Lower weight, Asian race, and adolescence were identified as negative predictors of etravirine exposure. An exposureresponse relationship was observed, with fewer participants achieving virologic suppression in the lower AUC 12 quartile (lowest AUC 12 quartile: ≤ 2704 ng•h/mL; virologic suppression: 41% vs. 67-76%) [34].…”
Section: Children/adolescentsmentioning
confidence: 91%
“…Subjects with hepatitis B virus co-infection had an 8.3% increase in etravirine CL/F, whereas those with hepatitis C virus co-infection had a 24% decrease in CL/F [24,33]. Etravirine PK exhibits relatively low interpatient variability (approximately 50% for CL/F); recent studies found approximately 13% and 5% of the interpatient variability in CL/F arises from concomitant ARVs and pharmacogenomics, respectively [34][35][36]. Steady-state PK parameters of etravirine in HIVpositive individuals are shown in Table 1.…”
Section: Pharmacokinetics In Hiv-positive Individualsmentioning
confidence: 99%
See 1 more Smart Citation